Introducing Students to the Challenges of Communicating Science by Using a Tool That Employs Only the 1,000 Most Commonly Used Words - Justin A. Pruneski (American Society for Microbiology, 2018)
Overcoming the complex and technical language used in science is a major barrier to scientists being able to communicate their work with the general public. This can lead to misunderstanding and mistrust of science, with many negative consequences. Scientists are increasingly seeking to improve their ability to communicate their work effectively with a variety of audiences. As such, students should recognize the challenges and importance of communicating science with nonscientists. This short classroom activity takes advantage of a free, web-based tool, called Simple Writer (https://xkcd.com/simplewriter/), which facilitates the writing and revising of text using only the 1,000 most commonly used words in English. Students are asked to write a paragraph in response to a prompt and use the Simple Writer tool to convert it into a form using only the 1,000 most commonly used words, while still maintaining the same message. By experiencing the difficulty of converting a relatively simple paragraph to meet to this criteria, students gain an appreciation for the challenge of removing jargon from scientific and other technical writing. Beyond the initial activity, the Simple Writer platform can be used in various other ways to engage students in learning science and developing essential writing skills.